SYSTEMATICS SIGNIFICANCE OF MORPHOLOGICAL AND ANATOMICAL DIVERSITY OF PORTULACA OLERACEA - Al-Newani, H. R. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to investigate the Portulaca oleracea is a succulent plant in Portulacaceae family distributed around different regions of Iraq as collected widely in the gardens of Baghdad governorate. The results of this study shown that a systematic significant of morphological and anatomical data. Individuals of purslane showed herb habit with branched shoot stems. Stems and leaves are glabrous and leaves are alternate, the petiole is absent. There is variation in morphological characters as (Flowers, inflorescence architecture), these inflorescences were viewed as clustered in the form of small one carrying many male and female flowers as the inflorescences take the form of long-stemmed. The flowering season for this species is from April till August as a weed in plains, however, anatomical techniques have been used as it revealed two patterns of stomatal complex, paracytic which is the most common followed by tetacytic is limited distributed type and it is recorded for the first time in this species. Druses crystals have been found distributed in the stem with angular collenchyma alternating with xylem parenchyma cells with large intercellular space. As well as, root anatomy has been done and the results showed casperian strips cells clearly in section with xylem and phloem regions.